Zastosowanie instrumentów marketingowych w kształtowaniu jakości usług hotelarskich - Jaremen, Daria E. (Application of Marketing Instruments in Developing the Quality of Hotel Services, 2005)
The necessity for winning competitive advantage by hotels directs their attention towards quality, which is more and more frequently referred to as the basis for their market success, and the best way for potential distancing rivals. The first good step on the road leading to quality improvement is the application of marketing orientation in an enterprise management. The article takes up an attempt of defining the importance of marketing instruments in the process of hotel services' improvement. There are also presented a few observations regarding the use of marketing in Polish hotel industry practice, as the method which facilitates the improvement of performed services quality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 143-153